Use of electrophysical agents by physical therapists in Brazil (Research, Society and Development, 2020)
Objective: to evaluate factors related with usage of Electrophysical Agents (EA) by Brazilian physiotherapists. Methodology: it was a cross-sectional and quantitative study, whose data were collected through an online questionnaire containing participants’ general, demographic and professional information, as well as questions related with usage of EA in physiotherapeutic clinical practice and factors related with non-usage and usage of these agents. Results: sample consisted of 407 physical therapists aged between 20 and 67 years (31.12 ± 7.72 years). Most participants completed their undergraduate studies in institutions located in Brazil Northeast region and presented some difficulties when using EA during their undergraduate. The specialization in trauma-orthopedics, professional performance in public services and usage of Transcutaneous Electrical Nerve Stimulation (TENS) in clinical practice were the most described. In addition, complications with EA usage were reported by respondents and most of them never took refresher courses on the topic after graduation. Conclusion: the results of the present study demonstrated that the availability and use of EA by physical therapists is not yet consolidated, being related with factors such as area of work, workplace and updates after graduation.